Increased risk of herpes zoster among 108 604 patients with inflammatory bowel disease. Issue 4 (13th December 2012) - Long, M. D.; Martin, C.; Sandler, R. S.; Kappelman, M. D.
Summary Background Patients with inflammatory bowel disease (IBD) on certain immunosuppressants have increased herpes zoster (HZ) risk. Aim To determine the risk of HZ in IBD and how antitumour necrosis factor‐alpha (anti‐TNF) agents affect this risk. Methods We performed a retrospective cohort and nested case–control study using administrative data from IMS LifeLink® Information Assets‐Health Plan Claims Database. In the cohort, we identified IBD patients <age 64 by diagnosis codes; matched to four individuals without IBD. HZ risk was evaluated by incidence rate ratio (IRR) and adjusted Cox proportional hazards models (HR). In the nested case–control analysis, 2659 IBD patients with HZ were each matched to four IBD patients without HZ. We determined associations between medications and HZ using conditional logistic regression. Results The cohort included 50 932 patients with Crohn's disease (CD), 56 403 patients with ulcerative colitis (UC) and 1269 with unspecified IBD, matched to 434 416 individuals without IBD. The IBD cohort had increased HZ risk compared with non‐IBD (IRR: 1.68, 95% CI: 1.60–1.76). After adjustment, IBD patients had a higher risk of HZ than non‐IBD (HR: 1.49, 95% CI: 1.42–1.57). In the nested case–control multivariate‐adjusted analyses, anti‐TNF medications (OR: 1.81, 95% CI: 1.48–2.21), corticosteroids (OR: 1.73, 95% CI: 1.51–1.99) and thiopurines (OR: 1.85, 95% CI: 1.61–2.13) were independently associated with HZ. Risk of HZ was highest with combination anti‐TNF and thiopurine therapy (OR: 3.29, 95% CI: 2.33–4.65). Conclusions Patients with inflammatory bowel disease are at increased risk for herpes zoster. Use of thiopurines, anti‐TNF agents, combination therapy and corticosteroids increases herpes zoster risk.